Middle Georgia and the approach of modernity : essays on race, culture and daily life, 1885/1945 - Van Hartesveldt, Fred R. (McFarland & Company, Inc., Publishers, 2018)
"This collection of new essays describes the lives of the common people of the day. A grisly mass murder underscored issues of race, class and poverty. African Americans struggled for self-betterment against the rise of Jim Crow. Women striving to overcome gender barriers found a hero in a pioneering Georgian female pilot."--